-6n+15=-5n-1

Simple and best practice solution for -6n+15=-5n-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6n+15=-5n-1 equation:


Simplifying
-6n + 15 = -5n + -1

Reorder the terms:
15 + -6n = -5n + -1

Reorder the terms:
15 + -6n = -1 + -5n

Solving
15 + -6n = -1 + -5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '5n' to each side of the equation.
15 + -6n + 5n = -1 + -5n + 5n

Combine like terms: -6n + 5n = -1n
15 + -1n = -1 + -5n + 5n

Combine like terms: -5n + 5n = 0
15 + -1n = -1 + 0
15 + -1n = -1

Add '-15' to each side of the equation.
15 + -15 + -1n = -1 + -15

Combine like terms: 15 + -15 = 0
0 + -1n = -1 + -15
-1n = -1 + -15

Combine like terms: -1 + -15 = -16
-1n = -16

Divide each side by '-1'.
n = 16

Simplifying
n = 16

See similar equations:

| 2(4-5x)+9=2x-23-8x | | 7(6x+7)=91 | | 5+6x=3+5x-8 | | 3x=2x-17.5 | | 2x/5-2x-1/2=x/5 | | 5*6+5x+6x=30x | | 7(8+x)=98 | | 4(x+3)+28=-4x | | -3x-8=5y+32 | | 6x=4y+8 | | (5x-2)(2x+7)= | | 4(y+3)=3y+13 | | 8(7-x)=4(3x-16) | | 8y-6=6y+6 | | 6(3+2x)=54 | | x^2-13x+15=-3x-1 | | 7x+2=12+x | | -16x-20=-13x+55 | | (a+b+c)*(a+b-c)= | | 7x^2+28x-315=0 | | 10=42-2x | | 7x+21=4+2x | | 6(7+2x)=114 | | 2x-3+5x-8=6x+54 | | x^2+4x+10=7 | | x^2+2x=1000 | | 5a-6=3a-8 | | 0=6x^2+5sp-6p^2 | | 8(e-1)=5e+2 | | 3x^2-54x+240=0 | | 6x^2+5sp-6p^2=0 | | 14x+1=21x+4 |

Equations solver categories